2020
DOI: 10.13005/bpj/2049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paronychia Argentea Extraction on Kidney Stone by Using Calcium Oxalate Method

Abstract: Urinary calculi are stones (urolithiasis) that can form anywhere in urinary tract outside of the kidneys and mostly composed of calcium oxalate and phosphate, additionally with elevated throughout the last two decades in the world. Chemical composition plays a major part in nephrolithiasis. Therefore, the high concentrations of lithogenic substances in urine enhance the crystallization method in urine tract system. The most kidney stones form from calcium oxalate, the present study was inspected the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, for intrarenal pyelolithiasis, staghorn calculi with multiple branches growing into different calyceal and multiple calyceal stones with secondary infundibulum stenosis or calyceal diverticulum, it is much more complicated, and laparoscopic pyelolithotomy alone may not be successful. Currently, intrarenal sinus peotomy or partial renal parenchyma incision becomes necessary [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for intrarenal pyelolithiasis, staghorn calculi with multiple branches growing into different calyceal and multiple calyceal stones with secondary infundibulum stenosis or calyceal diverticulum, it is much more complicated, and laparoscopic pyelolithotomy alone may not be successful. Currently, intrarenal sinus peotomy or partial renal parenchyma incision becomes necessary [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,34 Last but not the least, several studies showed that the fractions of the total extract of this plant has high potency in treatment of kidney stones (calcium oxalate and calcium phosphate); mainly those fractions contains non-polar and semipolar compounds of this plant. 35,36…”
Section: Antioxidant and Anti-inflammatory Activitiesmentioning
confidence: 99%